Assessing Outcomes of Online Training in Public Health: Changes in Individual and Organizational Knowledge and Capacity - John W. Wallace; Jennifer A. Horney; Rachel A. Wilfert; Lorraine K. Alexander (MDPI AG, 2013)
The need for a well-prepared public health workforce to prepare for and respond to threats of terrorism, infectious diseases, and other public health emergencies is well documented, as is the reality that the public health workforce in the United States is under-trained and unprepared to handle public health emergencies. The impact of training on the public health workforce is often measured by the volume of training completed and post-course evaluation data. A survey of current, high-volume users (n = 759) of the University of North Carolina Center for Public Health Preparedness Training Web Site, defined as individuals who had completed 12 or more training modules was conducted in order to determine if measurable changes in preparedness and response knowledge and capacity were brought about by the trainings. Two-hundred and seventy respondents completed the survey (response rate = 36%), with 52% reporting employment in governmental public health. Individual changes reported as a result of training included increased personal satisfaction (71%), increased job satisfaction (38%), and recognition by supervisors for training completion (23%); Organizational changes included updates to training plans (19%), making trainings mandatory (19%), and revising standard operating procedures (13%). Results from this survey indicate that the knowledge learned from completing online trainings led to changes in individuals and, to a lesser extent, changes in organizations.